The Role of Creative Entrepreneurship Education Among Millennials and Generation Z - Herlianti, Anggun Oktavia; Gustari, Tresna Dita; Hamdani, Nizar Alam; Nurdianti, Ica Sri (Entrepreneurship Faculty, Universitas Garut, 2024)
Generation Z, known as digital natives, requires an educational approach that is more innovative and relevant to their technology usage habits. The purpose of this study is to analyze the role of creative entrepreneurship education for the millennial generation and generation Z which can increase their competitiveness in an increasingly competitive market. The research method used is a qualitative approach to systematic literature review design with analysis of observation results using publish or perish software, data collection techniques are carried out through observation, interviews and documentation studies, then data analysis uses data triangulation. The results of the data analysis can be identified that entrepreneurship education plays a role in the creative efforts of the millennial and generation Z generations to take concrete steps in opening up business opportunities amidst existing potential and challenges.